Botulinum Neurotoxin Type A for the Treatment of Benign Prostatic Hyperplasia: Randomized Study Comparing Two Doses - René Arnouk; Carlos Henrique Suzuki Bellucci; Roberto Benatuil Stull; José de Bessa Junior; Cesar Augusto Malave; Cristiano Mendes Gomes (The Scientific World Journal)
Purpose. To assess the efficacy and safety of intraprostatic injection of two botulinum neurotoxin type A (BoNT-A) doses for the treatment of benign prostatic hyperplasia (BPH). Materials and Methods. Men with symptomatic BPH who failed medical treatment were randomized to receive 100 U or 200 U of BoNT-A into the prostate. The International Prostatic Symptom Score (IPSS), maximum flow rate (Qmax), post-void residual volume (PVR), PSA levels and prostate volume before injection and after 3 and 6 months were evaluated. Adverse events were compared between the groups. Results. Thirty four patients were evaluated, including 17 in the BoNT-A 100 U group and 17 in the BoNT-A 200 U group. Baseline characteristics were similar in both groups. Both doses produced significant improvements in IPSS, Qmax and PVR after 3 and 6 months and both doses promoted comparable effects. Prostate volume was affected by 200 U BoNT-A injection only after 6 months of treatment. PSA levels were significantly affected in the 100 U group only after 6 months of treatment. In the 200 U group, PSA levels were significantly decreased after 3 and 6 months. The complication rate was similar in both groups. Conclusions. Efficacy and safety of both BoNT-A doses are similar for BPH treatment in the short term followup.